2012
DOI: 10.1007/s13139-012-0181-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Combined Metabolic–Volumetric Indices of 18F-FDG PET/CT for the Early Prediction of Neoadjuvant Chemotherapy Outcomes in Breast Cancer

Abstract: Purpose The purpose of this study was to investigate the usefulness of metabolic-volumetric indices of 18 Ffluorodeoxy-D-glucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) for the evaluation of neoadjuvant chemotherapy outcomes in breast cancer. Methods Twenty-four patients with locally advanced breast cancer were enrolled in the study. They underwent baseline 18 F-FDG PET/CT scan and received four or six cycles of neoadjuvant chemotherapy, interim 18 F-FDG PET/CT was done after seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
(57 reference statements)
1
26
0
Order By: Relevance
“…Although there was no reduction in the size of her thyroidal and mediastinal masses, there were significant decreases in SUVmax in both sites and the area of FDGpositivity in her mediastinal mass, indicative of reduced inflammatory activity in keeping with a treatment response. It is of interest that reduction of SUVmax is at least as clinically important as tumor size as an index of oncological response (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no reduction in the size of her thyroidal and mediastinal masses, there were significant decreases in SUVmax in both sites and the area of FDGpositivity in her mediastinal mass, indicative of reduced inflammatory activity in keeping with a treatment response. It is of interest that reduction of SUVmax is at least as clinically important as tumor size as an index of oncological response (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the PET studies in patients who have undergone NAC have common limitations of small patient numbers, variable cutoff value of percentage change in the standardized uptake value (SUV), and limited use of metabolic response parameters with only SUV. Recent studies showed that the relative decrease in volume-based PET parameters after two cycles of NAC could be used to predict pathologic complete response more accurately than SUV (6)(7)(8). Many investigators studied only the association between PET parameters and pathologic complete response and did not evaluate the relationship between PET parameters and prognosis in patients who failed to achieve pathologic complete response.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…18 F-FDG PET data allow a quantitative evaluation of glucose metabolism of tumor. Although a lot of previous studies have reported the clinical usefulness using SUV max and volumetric parameters, these conventional parameter-based analyses have several limitations [4,5,[11][12][13]. These parameters are classified into histogram-based parameters, so they also have the short-comings of histogram analysis.…”
Section: Patientsmentioning
confidence: 99%